Marine resources of islands: status and approaches for sustainable exploitation/conservation with special emphasis to Andaman and Nicobar - ROY, S DAM; GEORGE, GRINSON (The Indian Journal of Animal Sciences, 2010)
Island ecosystem is unique but with a great diversity. Marine resource potential of Andaman and Nicobar Islands (ANI) is underutilized. The sensitive ecosystems of corals and Mangroves are facing threats as a result of changing climate. Potential fishery resources need to be exploited in sustainable manner for income and employment generation of islanders. Primary data on resources of Bay Islands are collected resorting to standard survey methods and secondary data are used as supporting data for analyzing the trend and potential of fisheries in ANI. The paper is depicting in details the major marine resources and their status in Bay Islands and approaches for their sustainable exploitation and conservation.